Comparing Surgical Site Occurrences in 1 versus 2-stage Breast Reconstruction via Federated EMR Network. Issue 1 (January 2021) - Singh, Devinder; Slavin, Benjamin R.; Holton, Tripp
Abstract : Background: TriNetX (TriNetX Inc., Cambridge, Mass.) is a federated electronic medical record network. The TriNetX system conducts customized search queries of over 36 million electronic medical records, and returns results in just minutes. To our group's knowledge, TriNetX has not been previously used in plastic surgery research. This study aimed to utilize a continuously updated federated network of 36, 000, 000 electronic medical records (TriNetX) for comparing 90-day postoperative outcomes between prosthetic breast reconstruction techniques. Methods: Using TriNetX, we analyzed the records of approximately 36 million patients in 31 health care organizations. The de-identified records of 18, 744, 519 women (age 18–9) were retrospectively screened. A cohort of 4747 patients with a diagnosis of malignant neoplasm of the breast, any stage, having undergone mastectomy, and breast reconstruction with tissue expander was compared with a second cohort of 870 patients diagnosed with malignant neoplasm of the breast, any stage, mastectomy, and immediate insertion of breast implant following mastectomy. Surgical site occurrences occurring within 90 days postoperatively were compared using propensity score matching. Results: Propensity score matching resulted in 870 patients in both well-balanced cohorts. There were no statistically significant differences between the balanced cohorts with respect to 90-day surgical site occurrences. Conclusions: TriNetX enables data-driven clinical research such as retrospective cohort comparison. During the 90-day postoperative period, there were fewer complications noted in the single-stage cohort for all outcomes studied; although this comparison was not statistically significant, we believe it demonstrates a clinically significant finding that single-stage direct-to-implant is at least as safe as the more complicated 2-stage approach.